Association of 2184AG Polymorphism in the RAGE Gene with Diabetic Nephropathy in Chinese Patients with Type 2 Diabetes. (3rd December 2015) - Cai, Wei; Li, Jian; Xu, Ji-Xiong; Liu, Ying; Zhang, Wei; Xiao, Jun-Ren; Zhu, Ling-Yan; Liu, Jian-Ying
Abstract : Objective . The interaction between advanced glycation end products and their cellular receptor (RAGE) has an important role in the pathogenesis of diabetic microvascular complications. The aim of this study was to investigate the relationship between the 2184A/G polymorphism in the RAGE gene and diabetic nephropathy in Chinese Han patients with type 2 diabetes mellitus. Methods . A total of 868 patients with type 2 diabetes mellitus (486 without and 382 with diabetic nephropathy) were enrolled in this study. The genotype and allele frequencies of the 2184A/G polymorphism were detected using the polymerase chain reaction-restriction fragment-length polymorphism method. Results . The G allele and AG + GG genotype frequencies in patients with diabetic nephropathy were significantly lower than those in patients without diabetic nephropathy (P = 0.001 andP = 0.005, resp.). After adjustments for possible confounders, multivariate logistic regression analyses showed that the 2184A/G polymorphism was independently associated with diabetic nephropathy (OR = 0.46, 95% CI: 0.22–0.92, P = 0.028 ). Conclusions . Our study indicated that the 2184A/G polymorphism in the RAGE gene was significantly associated with diabetic nephropathy in Chinese Han patients with type 2 diabetes.